Hong Kong sports policy: Reforming the triangulation of community sports, elite sports, and major sports events (CEM) - Chong, D.; Fok, A.; Liang, W. (Path of Demoracy; HK Academy of Politics & Public Policy, 2023)
Sports regulations, policies and organisational structures are fundamentals for successful sports coordination and development, contributing to the flourishing and well-being of both individuals and whole societies. Hong Kong Sports Policy of community sports (C), elite sports (E) and major sports events (M) have had remarkable achievements in recent years. Given the background of a new Culture, Sports and Tourism Bureau will be established to better safeguard the development of sports in Hong Kong. The current study aims to gain more understanding of current problems of the Hong Kong Sports Policy and to propose effective and pragmatic suggestions for addressing the existing problems. A qualitative research design has been used in this research. A proposed CEM framework was developed, offering potential guidelines for its future rollout. Key recommendations include: (1) Establishing the Culture, Sports, and Tourism Bureau with a clear blueprint, periodic CEM reviews, enhanced management over SF&OC and NSAs, and promoting Chinese Sports Tourism; (2) Bolstering sports culture by raising citizen awareness, partnering with RTHK, and involving higher-ed students as event volunteers; (3) Increasing support for emerging elite sports; (4) Introducing sponsorship platforms like the New Sports Pilot Scheme; and (5) Elevating professional standards in coaching, training, and facilities management.